PENGARUH STIMULASI METODE FLOOR TIME TERHADAP PERKEMBANGAN ANAK BATITA - Santoso, Sabar; Muslihatun, Wafi Nur; Santi, Mina Yumei (Jurnal Kesehatan Ibu dan Anak, 2014)
Parents have a major role in stimulating and developing the potential of children's intelligence. One of the methods that used to stimulate children's intelligence and potential is floor time. The aim of this study is to determine the effect of stimulation of floor time in the development of toddlers. The development of toddlers before stimulation in the treatment group with the most dubious result, while in the control group with the most appropriate result. For developments after stimulation in the treatment group was given an increase that has become more appropriate results whereas in the control group there is a small increase. The test results showed that the level of child development child development at pretest has a minimum value of 6 and a maximum value of 10 with an average value of 8.56 and the pretest and post-test 9.66 and the maximum value of the difference between the minimum value of 1.1. The results of tests of significance with the Wilcoxon signed rank test (p) = 0.00 and the Friedman test (p) = 0.00 , indicates that the value (p) < 0.05, which means it can be descript in the treatment group contained a significant influence in the administration method floor time to the development of toddler. The result of tests of significance on the child's age, maternal age, maternal education and maternal employment does not give effect to the development of toddler. There stimulatory effect of floor time to the development of a toddler is very significant.